Liquidity Effects of a Wealth Tax on Residential Rental Real Estate - Maiterth, Ralf; Piper, Yuri; Sureth-Sloane, Caren
This article examines the liquidity effects of a wealth tax on residential rental real estate. Using data from a real estate corporation, we simulate the effects of a wealth tax on cash flows from the rental operations. The level of detail of the data enables us to conduct analyses at the annual, regional and year of construction level. A comparison with real estate data from other sources supports external validity. The results of the simulation show that the introduction of a wealth tax can significantly reduce the cash flow from rental operations and lead to liquidity problems. On average over all observations, a wealth tax rate of 2% leads to a negative cash flow after all costs. In general, this finding implies that growth-oriented real estate is more affected by a wealth tax in terms of liquidity than rental yield-oriented real estate. Particularly in large cities with high market values but relatively low rents, the liquidity effects can be more than three times as high as in rural or industrial regions – potentially leading to a relative loss of investment attractiveness. As a wealth tax is decoupled from rental income, the tax burden is very sensitive to market developments, including the interest rate environment. As a result, investments in residential rental real estate are exposed to additional uncertainty. This additional tax uncertainty might impair the willingness to invest and should therefore be taken into account in political discussions on the reintroduction of a wealth tax.

Schocks durch Zölle und Steuern. Handelskonflikte und Abkommen werden zur zentralen Frage für Unternehmen. Wie bewältigen sie die neue Unsicherheit? - Kombert, Sounia; Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Steuerkomplexität: Wie lässt sie sich messen und welche Folgen hat sie? - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Banks' tax disclosure, financial secrecy, and tax haven heterogeneity - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren (Journal of International Accounting, Auditing and Taxation (JIAAT))

Determinants of Tax Complexity: Evidence from a Developing Country - Schipp, Adrian; Siahaan, Fernando; Sureth-Sloane, Caren (Intertax)
This study investigates the determinants of tax complexity in Indonesia, focusing on the perspectives of tax officers and firms, and thus provides a case study relevant to developing countries. Understanding tax complexity in this context is crucial as developing nations frequently encounter legislative, fiscal, and administrative challenges that exacerbate their tax complexity. Complexity can hinder investment, impair tax revenue collection, and impede economic development. The authors adapt a global survey instrument to the Indonesian context and collect responses from Indonesian tax officers and firms. Transfer pricing is perceived as the most complex tax regulation which is consistent with cross-country studies. However, in contrast to the global findings, statutory tax rates and taxes on dividends rank second and third in Indonesia. While Indonesian tax officers emphasize the complexity of transfer pricing regulations, firms are more concerned about the complexity of tax procedures, especially tax guidance and tax audits. Furthermore, comparative analyses show that tax officers perceive tax regulations as being more complex than tax procedures. In contrast, firms perceive the opposite, particularly for tax audits. The findings offer a nuanced picture of tax complexity in a developing country and provide guidance for tax reforms in Indonesia. They also serve as a commencement for further analyses of developing countries.

Preferences for Taxing Wealth and Income - Maiterth, Ralf; Piper, Yuri; Schneider, Cornelius
We examine German individuals' preferences for income and wealth taxation and, importantly, the interplay between these two tax instruments. While prior research often examines wealth tax preferences in isolation, actual tax systems consist of multiple interacting taxes. To capture this dynamic, we elicit preferred tax burdens in a large-scale online experiment with 2,702 participants randomly assigned to one of four treatment groups: respondents state either an unspecified overall tax burden, separate income and wealth tax burdens, an income tax burden only, or a wealth tax burden only. Our baseline estimates reveal average (marginal) tax rates of approximately 17.4% (18.9%) for income and 4.1% (2.3%) for wealth. We find that participants associate wealth with an ability-to-pay taxes: when a wealth tax is not explicitly available, preferred income tax rates are approximately 30% higher. However, when both instruments are available, participants do not treat them as substitutes. Instead, they appear to treat the two taxes as separate mental bins: the standalone income and wealth tax burdens are combined in a notably additive manner, resulting in a significantly higher overall tax burden. Further, respondents apply implicit exemptions for low levels of wealth and favor a wealth tax base focused primarily on financial assets and real estate other than the primary residence.

Neue Mikrodaten zu Unternehmensinsolvenzen in Deutschland: Die insol Datenbank - Rahali, Mahdi; Beyer, Bianca; Gassen, Joachim; Geschonke, Sebastian

COVID-19 insolvency moratoria, firm selection, and allocative efficiency - Rahali, Mahdi

Steuern, Standort, Unternehmensstrategie – Wie wettbewerbsfähig sind Deutschlands Steuer-, Zoll- und Investitionspolitik? - Kaeser, Christian; Schanz, Deborah; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Mandatory Binding Arbitration – Economic Evaluation of an International Norm - Danner, Christian; Lagarden, Martin; Martini, Jan Thomas; Niemann, Rainer; Oestreicher, Andreas; Sassmann, Juliane; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren; Voeller, Dennis (International Transfer Pricing Journal)

Steuern und Zölle als strategische Entscheidungsgrößen: Wirkungen auf Investitionen, Lieferketten und den Standort Deutschland - Koch, Reinald; Sureth-Sloane, Caren (Der Betrieb)

Navigating Transfer Pricing Complexity: Standardization, Cooperation, Transparency - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (eJournal of Tax Research)
This study examines the drivers of perceived corporate transfer pricing complexity. Our analysis is based on survey data from multinational firms in the manufacturing sector. We identify three key strategies expected to reduce transfer pricing complexity and associated compliance costs while enhancing tax compliance: standardising transfer pricing documentation, strengthening cooperation between tax authorities, and increasing transparency through expanded information exchange among tax authorities and between tax authorities and firms. The findings provide evidence-based insights for international tax policy aimed at reducing transfer pricing complexity and associated administrative burdens for both firms and tax administrations.

Steuersicherheit als Standortfaktor: Planbarkeit statt Investitionshemmnis - Sureth, Caren (Betriebs-Berater)

Application of Novel Exponential (Semi-)Parametric Short and Long Memory GARCH Models under Regulatory Requirements of Basel III - Hanke, Dominik Christian; Uhde, André; Feng, Yuanhua
This paper evaluates the forecasting performance of an expanded class of (semi-)parametric GARCH models belonging to the EGARCH family (EGF), including recently introduced long and short memory specifications and their semiparametric extensions. The semiparametric variants employ a multiplicative volatility decomposition into conditional and slowly varying unconditional components, where the latter is estimated via a data-driven local polynomial smoother to accommodate non-stationarities commonly observed in financial time series. Based on the revised Basel Committee framework for market-risk assessment, all models are capable of producing rolling one-day-ahead forecasts for Value at Risk (VaR) and Expected Shortfall (ES) under a wide range of symmetric and skewed innovation distributions. Their forecasting accuracy is examined using the regulatory traffic light tests for VaR and the recently developed ES-specific traffic light procedure, complemented by the regulatory loss function. In addition, model selection incorporates both a recently proposed corrected firm-oriented loss function that accounts for opportunity costs and the Weighted Absolute Deviation (WAD) criterion. The empirical comparison demonstrates that (semiparametric) long memory GARCH models - particularly those combining fractional dynamics with nonparametric scale adjustments - can serve as valuable alternatives to traditional parametric short memory models, offering more stable volatility estimates and improved tail-risk forecasts for practical risk management applications.
Keywords: semiparametric GARCH extension; data-driven local polynomial smoother; long memory; GARCH models; Value at Risk; Expected Shortfall; traffic light test; backtesting; Basel III; market risk

Comparing the behaviors of some original short and long memory exponential volatility models - Hanke, Dominik Christian; Feng, Yuanhua; Uhde, André
Volatility modeling is utilized across numerous fields including finance, environmental studies, and social sciences. It is particularly relevant in scenarios where understanding and predicting conditional variability is crucial, such as when dealing with incremental or time-dependent data. In this paper, novel short and long memory volatility models of the EGARCH family are introduced and analyzed, which are closely related to the well-established EGARCH model proposed by Nelson (1991) but share desirable theoretical properties in several dimensions. Recently developed members of the so-called EGARCH family, which introduces a modulus-log transformation proposed by John and Draper (1980) and a power transformation for the size and magnitude effect to tackle the problem with near-zero innovations and the asymmetric impact of positive and negative shocks on the volatility, are discussed. After a theoretical discussion of the proposed and related volatility models, the practical performance of the elaborated volatility models is compared to well-established and traditional GARCH approaches. A general QMLE algorithm is proposed to estimate the model parameters. The practical relevance of the advanced models is illustrated through a comparative study. By applying these volatility models to a variety of international stock index returns, this paper identifies market-specific characteristics as well as unique strengths and weaknesses of discussed volatility models. Although the practical performance of the recently introduced models is comparable to those obtained by the traditional EGARCH model, they generally outperform traditional non-exponential volatility models used as benchmarks and thus provide a useful alternative to existing short and long memory volatility models.
Keywords: Modulus Log-GARCH; Modified (FI)EGARCH; Modulus asymmetric (FI)Log-GARCH; (FI)EGARCH; long memory; modulus-log transformation; QMLE; model selection; implementation in R

Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska

The Role of Stakeholders in CSR Reporting of Non-Listed Banks - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska (Accounting in Europe)
We investigate the role of stakeholders in the CSR reporting of non-listed savings banks in Germany. They are established by municipal trustees and serve clients in their distinct operating area. Reporting discretion under the Non-Financial Reporting Directive may lead to variation in CSR reporting due to differences in sustainability interests of banks’ stakeholders and CSR governance (e.g. existence of a CSR manager). We document that the CSR reports and specific CSR dimensions are intensely associated with the existence of strong CSR governance and to a lesser extent with the interests of municipal trustees and bank clients. However, the associations with these stakeholders are predominantly present in banks with strong CSR governance. Our findings inform policy discussions about detailed CSR disclosure requirements (e.g. the European Sustainability Reporting Standards) and extension of reporting scope to firms with regional orientation and absence of typical shareholders.

Cost of debt for private firms revisited: voluntary audits as a reflection of risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa (International Review of Economics & Finance)
We examine the relation between voluntary audit and the cost of debt in private firms. We use a sample of 7420 small private firms operating in the period 2006-2022 that are not subject to mandatory audits. Firms self-select into voluntary audits because of the economic setting (e.g., ownership complexity, export, subsidiary status) or because firm fundamentals limit their access to financial debt. In the outcome analyses, we find that voluntary audits result in higher, rather than lower, interest rates with increases ranging from approximately 1.7 percentage points, but going higher depending on the exact specification. This effect is present regardless of the perceived audit quality (Big-4 vs. non-Big-4), consistent across auditor types. Audited firms’ earnings are less informative about future operating performance. Voluntary audits facilitate access to financial debt for high-risk firms. The price paid is reflected in higher interest rates for voluntary audits – firms with higher information/fundamental risk.